Production performance of morkaraman, akkaraman and awassi sheep under semi-intensive conditions ii. growt and sııni«ıl kates of lambs - Orhan Özbey; Abdulkadir Akçan (Eurasian Journal of Veterinary Sciences)
The current study was conducted In order to investigate the growth and survival ability characteristics of Morkaraman, Akkaraman and Awassi lambs. In this study. 30 Morkaraman, 32 Akkaraman and 41 Awassi male and female lambs were used. İn Morkaraman, Akkaraman and Awassi lambs, birth weights were found as 3.71, 4.47 and 4.03 kg, weaning weights (105 th day) 24.12. 26.68 and 22.56 kg, daily live weight gains from birth to weaning 194.38. 211.52 and 176.48g and survival ability until the weaning period 87 %. 88 % and 88 %, respectively. While the effect of genotype throughout the growth period was found to be insignificant, that of parturition type was significant on day 45th (P<0.05), very significant on days 60th , 75th , 90th and 105th (P<0.01) and extremely significant at parturition and on day 30th (P<0.001). Days 90th (P<0.01) and 105th , on which influence of sexual period was found to be efficent, had on important effect in favour of male lambs.Effect ol mother's age was found to be significant (P<0.05) on days 75th and 90th.